MUSCARINIC ACETYLCHOLINE RECEPTORS AS TARGETS FOR DRUG DEVELOPMENT - Stojkovic, Maja; Trailović, Saša; Protic, Dragana (Medicinski podmladak, 2024)
Muscarinic acetylcholine receptors (mAChRs) are a subfamily of G protein-coupled receptors that have been identified as promising targets for drug development. Five different mAChR subtypes regulate various fundamental functions. In the central nervous system (CNS), they play a crucial role in regulating numerous cognitive, behavioral, and autonomic functions. Outside the CNS, they facilitate the effects of acetylcholine in organs and tissues innervated by parasympathetic nerves, participating in various vegetative functions such as regulating heart rate, smooth muscle contraction, and glandular secretion. The disruption in cholinergic signalling contributes to several pathophysiological conditions and diseases. Thus, muscarinic agonists and antagonists have a wide therapeutic potential in the treatment of neuropsychiatric disorders, such as Alzheimer’s disease, schizophrenia or pain, and also in diseases like COPD and incontinence. Activation of different mAChR with selective ligands could be beneficial for treating the above-mentioned diseases while avoiding side effects. Clinical trials targeting mAChRs have shown promising results, with several compounds demonstrating efficacy and better tolerability profiles. However, developing drugs targeting mAChR still presents challenges, primarily due to the high homology in the structure of the orthosteric binding site. The recent insights into the physiology, pharmacology, and structure of mAChRs have provided opportunities for the development of novel drugs targeting these receptors, including allosteric modulators. Allosteric modulators offer the advantage of selective binding mAChR, potentially enhancing therapeutic efficacy while minimizing off-target effects. In conclusion, mAChRs represent promising targets for drug development. Further research and clinical trials are needed to develop effective therapies targeting muscarinic receptors for a various diseases.